1984
DOI: 10.1177/000331978403501001
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes of Collagen and Elastin Content in Human Aorta and Pulmonary Artery

Abstract: Collagen and elastin in the arterial wall are thought to show some age-dependent changes, and to relate with development of the arteriosclerotic lesion. Both aortas and the pulmonary trunks were collected from 137 autopsy cases. Biochemical determination of collagen and elastin content was carried out. Collagen and elastin of the aorta and the pulmonary artery showed no significant age-dependent changes. Elastin content of the pulmonary artery increases with age in the adult. This paper seems to be the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 11 publications
5
70
1
Order By: Relevance
“…However, r 2 =0.5 means that 50% of the difference in distensibility was accounted for by age. The present data are in line with a number of earlier observations, obtained both in vitro and in vivo [9,10]. PASIERSKI et al [12], however, employing the conventional ultrasound M-mode technique for measuring vessel diameter, found that the elastic modulus (the ratio of pulmonary arterial pressure to vessel wall strain) was independent of age, and was related only to pulmonary arterial pressure.…”
Section: Influence Of Agesupporting
confidence: 93%
See 2 more Smart Citations
“…However, r 2 =0.5 means that 50% of the difference in distensibility was accounted for by age. The present data are in line with a number of earlier observations, obtained both in vitro and in vivo [9,10]. PASIERSKI et al [12], however, employing the conventional ultrasound M-mode technique for measuring vessel diameter, found that the elastic modulus (the ratio of pulmonary arterial pressure to vessel wall strain) was independent of age, and was related only to pulmonary arterial pressure.…”
Section: Influence Of Agesupporting
confidence: 93%
“…The age dependence of pulmonary arterial wall distensibility is another controversial issue. Although in vitro studies have shown that the pulmonary arterial wall stiffens with age [9,10], in vivo studies have produced equivocal results; a negative correlation between pulmonary compliance and age was reported in one study [11] but no such relation was found in another [12].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…9,10,32 For example, the elastin/collagen ratio of the aorta is of 1.5, whereas that of the femoral artery is 0.5 (see ref. 33). This ratio is also altered during arterial aging and by the atherosclerotic process, and fragmentation of the elastic fiber network leads to premature recruitment of the most rigid collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial collagen concentration has been reported to: steadily increase, to increase only after the age of 50 and to remain unchanged with age (Cattell et al 1996;Hosoda et al 1984;Maurel et al 1987). Although elastin concentration in ageing arteries has been reported to decrease (Hosoda et al 1984;Maurel et al 1987), in the specific case of normotensive individuals, aortic elastin concentration appears to increase (Cattell et al 1996). Cattell and co-workers highlight the need to distinguish between changes in the absolute amount of a tissue component versus changes in its concentration (Cattell et al 1996).…”
Section: Vascularmentioning
confidence: 99%